False positive elevation in serum creatinine: a case report - Oliveras, Laia; Coloma, Ana; Escartín, Teresa; Castro, Maria José; Vicente, Natalia; Gomà, Montse; Cruzado, Josep Maria (Frontiers in Medicine, 2024)
Background Paraproteins can interfere with several substances, producing erroneous laboratory measurements. The diagnosis of kidney disease in patients with hematological disorders has important prognosis implications. An elevated creatinine with no other signs of kidney disease should prompt the idea of a spurious creatinine. Communication between the clinical team and the laboratory is key. Case presentation In this case, we present a 68-year-old woman with an elevated creatinine and an IgM lambda paraprotein. Interestingly, there were no other signs of chronic kidney disease besides the creatinine value, with no albuminuria or microhematuria. A kidney biopsy showed normal parenchyma and ruled out the possibility of paraprotein-related damage. The monoclonal component and creatinine levels raised parallelly during follow-up while maintaining normal urea levels. This prompted the hypothesis of a falsely elevated creatinine. It was confirmed with a normal glomerular filtration rate determined by a radioisotope, a cystatin C measurement and a reduction in creatinine when diluting the sample. Conclusion It is important to consider the possibility of a falsely elevated creatinine in patients with paraproteinemia and no other signs of kidney disease to avoid unnecessary diagnostic tests and for the prognostic implications.